Robustness analysis of a steering-based control strategy for improved lateral performance of a truck-dolly-semitrailer. (2015) - Kharrazi, Sogol; Lidberg, Mathias; Fredriksson, Jonas
A control strategy for lateral performance improvement of a truck-dolly-semitrailer combination by active steering of the towed units is presented. The effectiveness and robustness of the controller are verified by extensive analysis of the controller performance in various driving conditions at high speeds and presence of uncertainties in vehicle parameters, such as tyre cornering stiffness and moment of inertia. It is shown that the controller reduces the yaw rate rearward amplification, offtracking and side slip angle significantly. It is also demonstrated that brake interventions by other controlling systems such as electronic stability control do not deteriorate the controller performance.